IMPLEMENTING PERSONAL VOCABULARY NOTES TO DEVELOP VOCABULARY MASTERY ON EIGHT GRADE STUDENTS OF SMP NEGERI 4 KADATUA - Baharudin Adu; Restu Oktafiani (English Education Journal, 2021)
The research is conducted to find out the significant difference between the vocabulary mastery of students who are taught using the personal vocabulary note method and those taught using conventional methods. This research used experimental design. The population in this research is 33 students of class VIII SMP Negeri 4 Kadatua that consisted of 2 classes. The sample was taken by using a sample group consisting of 16 students in the experimental class, and 17 students for the control class. The instrument used in this study was a vocabulary test. The results of this study indicate that: 1) the mean score of the pretest in experimental class was 43.18 and the final test was 71.87; 2) the mean score of the control class in pretest was 44.70 and the final test was 64.11; and 3) Hypothesis testing has a significance of 0.23 which is smaller than α 0.05. Based on these results, it can be concluded that there is a significant difference in the vocabulary mastery of students who are taught using the personal vocabulary note method and taught using conventional methods in class VIII students of SMP Negeri 4 Kadatua.